Wind generator Co-simulation with fault case analysis - Makolo, Peter (My University, 2013)
As machine designs are becoming more complex and sophisticated, the process of verifying these designs and hence developing control strategies are therefore becoming more complicated, expensive and time consuming. In order to better understand the physics in complex machine designs, first-order harmonic models within dynamic simulations are becoming insufficient. However, co-simulation is now a proven way to handle and understand the physics of these complex machine designs. In this project, a finite-element-method model of a permanent magnet synchronous generator is developed. The generator model is then embedded/coupled with a PI control system model which is developed in Simulink. The process of coupling is facilitated with the use of Simplorer which links these two models. The complete embedded/ coupled model is then simulated for a conventional torque control strategy of the generator. A fault case is introduced in the simulation in order to understand control strategies for the machine. Finally, simulation results indicate that it is possible to co-simulate a PMSM using Maxwell embedded in Simulink control system using Simplorer.
Keywords: Elkraftteknik; Electric power engineering